2022
DOI: 10.1126/scitranslmed.abi4632
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory CD20 + T cells contribute to CNS-directed autoimmunity

Abstract: The origin and function of CD20 + T cells are poorly understood. Here, we characterized CD20 + T cells in mice and humans and investigated how they are affected by anti-CD20 antibody treatment. We report that murine CD20 + T cells are unable to endogenously express the B cell lineage marker CD20; the development of CD20 + T cells in rodents requires the presence of CD20-expressing B cells. Our results demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…As the B-cells are the main expressors of the CD20 marker, the anti-CD20 monoclonal antibodies primarily affect the B-cell compartment of the immune system—although some recent literature suggests that their effectiveness in MS may stem from their effect on subsets of ‘rogue’ CD20+ T cells 50. Similar to pwMS on other DMTs, the COVID-19 vaccines’ immunogenicity among pwMS on aCD20 could be considered a translation of the previously-determined B-cell and T-cell dynamics in them,34 51 based on which the current guidelines recommended a 12-to-36-week window between aCD20 infusion and COVID-19 vaccination 1–4.…”
Section: Resultsmentioning
confidence: 99%
“…As the B-cells are the main expressors of the CD20 marker, the anti-CD20 monoclonal antibodies primarily affect the B-cell compartment of the immune system—although some recent literature suggests that their effectiveness in MS may stem from their effect on subsets of ‘rogue’ CD20+ T cells 50. Similar to pwMS on other DMTs, the COVID-19 vaccines’ immunogenicity among pwMS on aCD20 could be considered a translation of the previously-determined B-cell and T-cell dynamics in them,34 51 based on which the current guidelines recommended a 12-to-36-week window between aCD20 infusion and COVID-19 vaccination 1–4.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence suggests that the latter may play an important role in the pathogenesis of MS and that the depletion of CD20-expressing T cells may account for part of the efficacy of anti-CD20 treatment. 15 It has further been shown that CD20 T cells repopulate at an earlier time point after pulsed BCDT than CD20 B cells. 16 Three months after rituximab infusion, counts of CD20 T cells were higher than the ones of CD20 B cells.…”
Section: Discussionmentioning
confidence: 96%
“…CD20 protein expression is absent on T cells of human cord blood, suggesting acquisition of this molecule later in development [ 6 ]. In mice, CD20 + T cells only appear in the spleen after week 2 of age supporting this notion [ 15 ]. By co-culturing T and B cell lines, de Bruyn et al [ 6 ] were able to show an increase in CD20 expression on T cells after just 1 h. They speculated that the mechanism of this was via trogocytosis when T cells make contact with their cognate B cells [ 6 ].…”
Section: Immunobiology Of Cd20 + T Cellsmentioning
confidence: 85%